2021
DOI: 10.20473/amnt.v5i2sp.2021.19-29
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Implementation of Fe Tablets for Adolescent Girl in 2019 at Pekanbaru City

Abstract: Background: The program for giving Fe tablets is one of the efforts to overcome anemia based on WHO recommendations, one of the targets is the adolescent girl. Indicators of the success of this program are decreasing the incidence of anemia in adolescent girls and increasing adherence to iron tablets consumption.  Objectives: This research aims to determine the implementation of the Fe tablets program for adolescent girls in 2019 in Pekanbaru City. Methods: This research uses a qualitative method which is then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…It is suggested that the importance of knowledge and understanding of adolescent school girls towards anemia may promote the adherence and outcomes post IFA supplementation. Lack of socialization about IFA and anemia to teachers and students, resulting to low knowledge of IFA and anemia as presented in quantitative key findings 19 . In this present study, only 31.1% students have obtained the information about anemia through media and it is in line with previous study that showed as many as 93.8% students did not expose by media health education about anemia and IFA at their school 18 .…”
Section: Knowledge On Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the importance of knowledge and understanding of adolescent school girls towards anemia may promote the adherence and outcomes post IFA supplementation. Lack of socialization about IFA and anemia to teachers and students, resulting to low knowledge of IFA and anemia as presented in quantitative key findings 19 . In this present study, only 31.1% students have obtained the information about anemia through media and it is in line with previous study that showed as many as 93.8% students did not expose by media health education about anemia and IFA at their school 18 .…”
Section: Knowledge On Anemiamentioning
confidence: 99%
“…Roles of teachers, parents, and health workers could be affected to the outcome, since the source of information related anemia were majority provided by the teachers (52.5%), health workers (39.3%), and parents (33.6%). A qualitative study at Pekanbaru City reported that there are still shortcomings in the procurement of informationeducation-communication media for the implementation, lack of coordination in implementing existing regulations 19 .…”
Section: Students' History Of Wifa Supplementationmentioning
confidence: 99%